Energy consumption model and its simulation for manufacturing and remanufacturing systems. Issue 5 (November 2016) - Wang, Xianlin; Luo, Wei; Zhang, Hua; Dan, Binbin; Li, Fei
Abstract This paper adopts a method of researching the process of energy consumption in manufacturing/remanufacturing systems to achieve lean energy. This method can be used in typical machining systems, especially including the machining process of manufacturing and remanufacturing. To validate this approach, we model and simulate the system with the DEVS theory and input-output model. This model establishes the machining process of a product. On the basis of work station, which is used for receiving work pieces and energy, exporting products and information of different kinds of energy consumption. We can simulate manufacturing/remanufacturing of integration machining process and material flow, information flow, and energy flow of the coupling process. After that, classify the energy consumption according to the quality of the products. The solutions, which are the margin of error between simulation and measurement, show that this method is effective. The output results help manage energy resource and provide train of thought for saving energy and reducing consumption.